High‐Polarity Fluoroalkyl Ether Electrolyte Enables Solvation‐Free Li+ Transfer for High‐Rate Lithium Metal Batteries. Issue 5 (19th December 2021) - Dong, Liwei; Liu, Yuanpeng; Wen, Kechun; Chen, Dongjiang; Rao, Dewei; Liu, Jipeng; Yuan, Botao; Dong, Yunfa; Wu, Ze; Liang, Yifang; Yang, Mengqiu; Ma, Jianyi; et al.
Abstract: Lithium metal batteries (LMBs) have aroused extensive interest in the field of energy storage owing to the ultrahigh anode capacity. However, strong solvation of Li + and slow interfacial ion transfer associated with conventional electrolytes limit their long‐cycle and high‐rate capabilities. Herein an electrolyte system based on fluoroalkyl ether 2, 2, 2‐trifluoroethyl‐1, 1, 2, 3, 3, 3‐hexafluoropropyl ether (THE) and ether electrolytes is designed to effectively upgrade the long‐cycle and high‐rate performances of LMBs. THE owns large adsorption energy with ether‐based solvents, thus reducing Li + interaction and solvation in ether electrolytes. With THE rich in fluoroalkyl groups adjacent to oxygen atoms, the electrolyte owns ultrahigh polarity, enabling solvation‐free Li + transfer with a substantially decreased energy barrier and ten times enhancement in Li + transference at the electrolyte/anode interface. In addition, the uniform adsorption of fluorine‐rich THE on the anode and subsequent LiF formation suppress dendrite formation and stabilize the solid electrolyte interphase layer. With the electrolyte, the lithium metal battery with a LiFePO4 cathode delivers unprecedented cyclic performances with only 0.0012% capacity loss per cycle over 5000 cycles at 10 C. Such enhancement is consistently observed for LMBs with other mainstream electrodes including LiCoO2 and LiNi0.5 Mn0.3 Co0.2 O2, suggesting the generality of the electrolyte design for battery applications. Abstract : This work designs an electrolyte system based on fluoroalkyl ether 2, 2, 2‐trifluoroethyl‐1, 1, 2, 3, 3, 3‐hexafluoropropyl ether (THE) to effectively upgrade the long‐cycle and high‐rate performances of lithium metal batteries. With THE rich in fluoroalkyl groups adjacent to oxygen atoms, the electrolyte owns ultrahigh polarity and enables solvation‐free Li + transfer with a substantially decreased energy barrier.